Pengelolaan Karakter Peduli Sosial Pada Anak Usia Dini Melalui Program Berjenjang - Umayah; Muhiyatul Huliyah; Heny Fajriani; Ridha Rahmawati (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study explains the management of social care character education in early childhood through a tiered program at Afta Islamic Kindergarten, Serang City. The research used a qualitative case study design. Data were collected from three key informants, namely the principal, a B2 classroom teacher, and the chairperson of the Parent-Teacher Association, through interviews, observation of school routines, and analysis of program documents. The findings show four activity tiers: annual, monthly, weekly, and daily. The annual tier consists of charity and iftar with orphans, the monthly tier provides supplementary healthy meals, the weekly tier uses Friday donations, and the daily tier includes watering plants, sharing food, and cooperative play. The program is planned through school work meetings, implemented through teacher modeling and habituation, and evaluated formatively through observation of children's behavior. The study highlights structured, collaborative, and child-centered character management